2011
DOI: 10.1016/j.bbr.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A reverse translational approach to quantify approach-avoidance conflict in humans

Abstract: Animal approach-avoidance conflict paradigms have been used extensively to characterize effects of anxiolytic agents and probe neural circuitry related to anxiety. However, there are few behavioral approaches to measure conflict in human populations, limiting the translation of findings from animal conflict tasks to human clinical research. We developed a novel approachavoidance conflict (AAC) paradigm involving situations in which the same decision is associated with "reward" (points) and "punishment" (negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
135
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(144 citation statements)
references
References 76 publications
9
135
0
Order By: Relevance
“…Such control of approach-avoidance behavior has been intensively studied in experimental animals (Amemori and Graybiel, 2012; Miller, 1971) and also in humans, in whom disturbances of such decision-making have been used as a marker for anxiety disorders (Aupperle et al, 2011; Dickson and MacLeod, 2004). Such a linkage to emotional decision-making and its frailty in some neuropsychiatric disorders accords with much work pointing to the medial prefrontal cortex as having abnormal activity in disorders such as obsessive-compulsive disorder (Fitzgerald et al, 2005), anxiety disorders (Pizzagalli, 2011) including post-traumatic stress disorder (Kasai et al, 2008), and addictive states (Goldstein et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Such control of approach-avoidance behavior has been intensively studied in experimental animals (Amemori and Graybiel, 2012; Miller, 1971) and also in humans, in whom disturbances of such decision-making have been used as a marker for anxiety disorders (Aupperle et al, 2011; Dickson and MacLeod, 2004). Such a linkage to emotional decision-making and its frailty in some neuropsychiatric disorders accords with much work pointing to the medial prefrontal cortex as having abnormal activity in disorders such as obsessive-compulsive disorder (Fitzgerald et al, 2005), anxiety disorders (Pizzagalli, 2011) including post-traumatic stress disorder (Kasai et al, 2008), and addictive states (Goldstein et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to scanning, subjects were trained on the AAC and completed three practice trials to ensure full understanding of the task. The AAC was conducted similar to previously described (Aupperle, et al, 2011) but with the addition of approach-reward trials. For each trial, participants were shown a runway with pictures on each side to represent two potential outcomes (Figure I).…”
Section: Methodsmentioning
confidence: 99%
“…We developed the approach-avoidance conflict (AAC) paradigm aimed at quantifying decision-making behavior during situations that involve conflicting outcomes that could motivate approach and/or avoidance behaviors (Aupperle, et al, 2011). We aim to add to the current approach-avoidance literature by examining decision-making behaviors during conflict – rather than focusing on trait motivations or approach versus avoidance learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such anxiety appears to be common among most anyone when approaching a novel situation, perhaps because of a tendency to appraise that novel situation as a threat (Gray & McNaughton, 2000). Additional evidence for this hypothesis is recent research showing an inverse relationship between self-efficacy and anxiety among university students (Ghaderi & Rangaiah, 2011) as well as research that ties anxiety directly to approach-avoidance conflicts (Aupperle, Sullivan, Melrose, Paulus, & Stein, 2011;Gannon, Roche, Kanter, Forsyth, & Linehan, 2011).…”
Section: Discussionmentioning
confidence: 99%